2001
DOI: 10.1148/radiol.2212000784
|View full text |Cite
|
Sign up to set email alerts
|

Image Quality and Dose Comparison among Screen-Film, Computed, and CT Scanned Projection Radiography: Applications to CT Urography

Abstract: S-F and CR provided better spatial resolution than did CT SPR. However, CT SPR provided improved low-contrast resolution compared with S-F, at exposures comparable to those used for S-F or CR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…These findings correspond with a former phantom study comparing 80 kV and 120 kV [31]. Doseadjusted CNR was higher the greater the slice thickness (2 mm versus 1 mm), as shown in the Siemens scanner with 100 kV and 120 kV.…”
Section: Possibilities Of Dose Reductionsupporting
confidence: 90%
“…These findings correspond with a former phantom study comparing 80 kV and 120 kV [31]. Doseadjusted CNR was higher the greater the slice thickness (2 mm versus 1 mm), as shown in the Siemens scanner with 100 kV and 120 kV.…”
Section: Possibilities Of Dose Reductionsupporting
confidence: 90%
“…The application of helical CT to the evaluation of the kidneys and urinary tract has been explored over the last 7 years and there is now a significant body of literature related to the investigation of urinary tract calculus disease, renal masses, renal vascularity and renal transplant donor imaging [1][2][3][4][5][6][7][8][9][10][11]. The primary advantage of MDCT over conventional helical scanning is the improvement in volume coverage combining speed with improved resolution allowing thinner slices.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al [12] demonstrated that at a variety of section thicknesses and table speeds, images of comparable diagnostic quality with less noise and similar artifact profiles to those from conventional helical CT were obtained using four-detector MDCT at 2-3 times the speed of a single-detector scanner from the same manufacturer. McCollough and Zink [13] showed better spatial resolution with MDCT compared with helical CT. McCollough et al [9] showed improved low-contrast resolution but not spatial resolution of CT urography compared with conventional IVU. McNicholas et al [8] demonstrated similar opacification of the calyces, collecting systems and proximal ureters with excretory helical CT urography using abdominal compression as that seen with conventional IVU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdominal CT and CTDR are performed with the same scanner, which avoids moving patients between different rooms. The spatial resolution of CTDR images is inferior to conventional radiographs, but contrast resolution and radiation exposure are similar [27,28,30,31]. Sudakoff et al have shown that CT urography plus repeated CTDR images during the excretory phase enable a more complete depiction of the urinary tract than with CT urography alone [28].…”
Section: Hybrid Techniquementioning
confidence: 99%